2021
DOI: 10.3346/jkms.2021.36.e182
|View full text |Cite
|
Sign up to set email alerts
|

Questionnaire-based Survey of Demographic and Clinical Characteristics, Health Behaviors, and Mental Health of Young Korean Adults with Early-Onset Diabetes

Abstract: Background The incidence of early-onset diabetes is increasing among young adults. However, there are limited data on the characteristics and management of young Korean adults with diabetes. This study assessed the clinical and demographic characteristics, health behaviors, and mental health among young Korean adults with diabetes mellitus. Methods This cross-sectional study included young Korean adults with diabetes (n = 225) with an onset age of 20–39 years from four … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“… 23 24 25 Targeting responsive patient groups to collect reliable answers is yet another challenge that can be addressed by distributing questionnaires to patients with good knowledge of their diseases, particularly those registering with university-affiliated clinics and representing patient associations. 26 27 28 …”
Section: Patient Knowledge and Perception Surveysmentioning
confidence: 99%
“… 23 24 25 Targeting responsive patient groups to collect reliable answers is yet another challenge that can be addressed by distributing questionnaires to patients with good knowledge of their diseases, particularly those registering with university-affiliated clinics and representing patient associations. 26 27 28 …”
Section: Patient Knowledge and Perception Surveysmentioning
confidence: 99%
“… 1 In addition, the prevalence of early-onset type 2 diabetes in adults diagnosed at age <40 years is being increasingly reported in Korea and worldwide. 2 3 Many studies have shown that early-onset type 2 diabetes manifested a more aggressive phenotype with worse glycemic control, shorter time to insulin initiation, and early development of complications 4 5 6 compared to late-onset diabetes. Our previous study showed that young adults with early-onset diabetes demonstrated poor health behaviors, such as smoking, less physical activities, skipping breakfast, and frequent mental depression.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study showed that young adults with early-onset diabetes demonstrated poor health behaviors, such as smoking, less physical activities, skipping breakfast, and frequent mental depression. 3 However, few studies have focused on diabetes self-care activities and barriers in patients with early-onset diabetes in Korea and around the world.…”
Section: Introductionmentioning
confidence: 99%